DNA and RNA Binding Proteins: From Motifs to Roles in Cancer - Bonczek, Ondrej; Wang, Lixiao; Gnanasundram, Sivakumar Vadivel; Chen, Sa; Haronikova, Lucia; Zavadil-Kokas, Filip; Vojtesek, Borivoj (International journal of molecular sciences, 2022)
DNA and RNA binding proteins (DRBPs) are a broad class of molecules that regulate numerous cellular processes across all living organisms, creating intricate dynamic multilevel networks to control nucleotide metabolism and gene expression. These interactions are highly regulated, and dysregulation contributes to the development of a variety of diseases, including cancer. An increasing number of proteins with DNA and/or RNA binding activities have been identified in recent years, and it is important to understand how their activities are related to the molecular mechanisms of cancer. In addition, many of these proteins have overlapping functions, and it is therefore essential to analyze not only the loss of function of individual factors, but also to group abnormalities into specific types of activities in regard to particular cancer types. In this review, we summarize the classes of DNA-binding, RNA-binding, and DRBPs, drawing particular attention to the similarities and differences between these protein classes. We also perform a cross-search analysis of relevant protein databases, together with our own pipeline, to identify DRBPs involved in cancer. We discuss the most common DRBPs and how they are related to specific cancers, reviewing their biochemical, molecular biological, and cellular properties to highlight their functions and potential as targets for treatment.
Keywords: cancer; targeted treatment; Neoplasms; DNA vazebné proteiny; DNA-Binding Proteins; Humans; mutation; RNA-Binding Proteins; nádory; proteiny vázající RNA; DNA/RNA binding protein; DNA; biomarkers; lidé; RNA